Analisis Pengaruh Mekanisme Good Corporate Governance terhadap Kinerja Keuangan - I Gusti Agung Ayu Pramita Indraswari; I G A N Alit Sumantri; I Gusti Agung Arista Pradnyani (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to analyze and empirically test the effect of Good Corporate Governance (GCG) mechanisms on financial performance as proxied by Return on Assets (ROA). The focus of the study is on manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2021-2024. The independent variables include the Board of Commissioners, Board of Directors, Managerial Ownership, and Institutional Ownership. Using a quantitative approach, this study utilizes 160 panel data observations analyzed through multiple linear regression. The results reveal that the Board of Commissioners and Institutional Ownership have a significant positive effect on ROA, indicating that effective internal and external oversight mechanisms can promote operational efficiency. However, the Board of Directors was found to have a significant negative effect, indicating that an overly large board creates bureaucratic inefficiency. Managerial Ownership did not have a significant effect on financial performance due to the low proportion of management ownership in the sample. Simultaneously, all GCG variables had a significant effect on ROA. In conclusion, strengthening the monitoring function through commissioners and institutional investors is crucial for profitability, while optimizing the number of directors is necessary to accelerate strategic decision-making in order to maintain the company's resilience in the global market.